Penyusunan Laporan Keuangan Berdasarkan SAK-ETAP: Studi Kasus UMKM Bebek di Mojosari - Regita Putri, Adinda; Setiono, Hari (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
This study aims to examine (1) the effect of education level on the application of financial statements based on SAK-ETAP on meat duck SMEs in Mojosari District. (2) The Effect of Business Size on the Recording of Financial Statements Based on SAK-ETAP on MSMEs broiler ducks in Mojosari District. (3) The Effect of Business Length on the Recording of Financial Statements Based on SAK-ETAP on MSMEs broiler ducks in Mojosari District. (4) The Effect of Guidance on Socialization and Information on the Recording of Financial Statements Based on SAK-ETAP on MSMEs of broiler ducks in Mojosari District. The research sample used was 50 MSMEs of broiler ducks. This research method uses primary method with data collection by questionnaire as a research instrument. Test the research instrument using validity test, reliability test. Hypothesis test using regression test which was preceded by normality test, autocorrelation test, multicollinearity test and heteroscedasticity test. Furthermore, hypothesis testing was carried out using multiple linear regression tests. The results showed that the level of education had a positive value of 0.245, the Business Size variable had a positive value of 1.399, the Length of Business variable had a positive value of 1.211, the Socialization and Information Development variable had a positive value of 0.257.